Vascular Repair by Grafting Based on Magnetic Nanoparticles - Xin Liu; Nan Wang; Xiyu Liu; Rongrong Deng; Ran Kang; Lin Xie (MDPI AG, 2022)
Magnetic nanoparticles (MNPs) have attracted much attention in the past few decades because of their unique magnetic responsiveness. Especially in the diagnosis and treatment of diseases, they are mostly involved in non-invasive ways and have achieved good results. The magnetic responsiveness of MNPs is strictly controlled by the size, crystallinity, uniformity, and surface properties of the synthesized particles. In this review, we summarized the classification of MNPs and their application in vascular repair. MNPs mainly use their unique magnetic properties to participate in vascular repair, including magnetic stimulation, magnetic drive, magnetic resonance imaging, magnetic hyperthermia, magnetic assembly scaffolds, and magnetic targeted drug delivery, which can significantly affect scaffold performance, cell behavior, factor secretion, drug release, etc. Although there are still challenges in the large-scale clinical application of MNPs, its good non-invasive way to participate in vascular repair and the establishment of a continuous detection process is still the future development direction.